2017
DOI: 10.1088/1361-6439/aa9a4e
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing microinjection molding replication quality

Abstract: In recent years, there has been increased interest in producing and providing high-precision plastic parts that can be manufactured by microinjection molding: gears, pumps, optical grating elements, and so on. For all of these applications, the replication quality is essential. This study has two goals: (1) fabrication of high-precision parts using the conventional injection molding machine; (2) identification of robust parameters that ensure production quality. Thus, different technological solutions have bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 36 publications
(40 reference statements)
1
17
0
Order By: Relevance
“…Indirect structuring refers to a textured surface that is subsequently coated with DLC, while direct structuring refers to the texturing of the DLC coating itself [191]. LST has been the most widely used technique for DLCs, for both indirect texturing [117,[194][195][196][197][198][199][200][201][202][203][204][205][206] and direct texturing [118,124,[207][208][209][210][211].…”
Section: Diamond-like Carbon and Surface Texturesmentioning
confidence: 99%
See 2 more Smart Citations
“…Indirect structuring refers to a textured surface that is subsequently coated with DLC, while direct structuring refers to the texturing of the DLC coating itself [191]. LST has been the most widely used technique for DLCs, for both indirect texturing [117,[194][195][196][197][198][199][200][201][202][203][204][205][206] and direct texturing [118,124,[207][208][209][210][211].…”
Section: Diamond-like Carbon and Surface Texturesmentioning
confidence: 99%
“…Since DLC films tend to be rather thin, conventional laser texturing techniques have not been very successful for direct texturing, leading to severe spalling [191]. Most successful reports of direct texturing of DLCs have been carried out using femtosecond pulsed lasers (due to reduced thermal effects) [124,209,212]. One alternative is direct laser interference patterning (DLIP) allowing for a fast fabrication of periodic patterns on macroscopic areas based on the interference of two coherent laser beams [118,192,210,211,213,214].…”
Section: Diamond-like Carbon and Surface Texturesmentioning
confidence: 99%
See 1 more Smart Citation
“…These cumulated effects generate this difficulty in micro-texture replication on the surface of a macroscopic part and therefore will limit functionalization quality of the part surface. [7] The creation of this frozen layer is also influenced by the injection velocity, which in multiple studies is shown to be a key process parameter in the replication quality of micro-features. [8] Nowadays, an injection molding simulation allows for a relatively reliable prediction of injection problems and this is done using the commercially available software.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, as the injected melt volume is extremely small, the surface-to-volume ratio increases, and thus a very fast solidification occurs, hindering the complete filling of the cavity [ 6 ]. Therefore, in order to favour the replication capability of the process, high levels of injection speed, melt temperature and mould temperature are typically required [ 7 , 8 , 9 ]. Since the levels of these parameters are superiorly limited by the occurrence of polymer degradation, the process window of µIM becomes narrower than that of IM, making process optimization a fundamental step for manufacturing products that comply with design specifications.…”
Section: Introductionmentioning
confidence: 99%